Biomechanical Effect of Medial Collateral Ligament Repair With and Without Suture Augmentation on Knee Laxity and Anterior Cruciate Ligament Force - Fidelius von Rehlingen-Prinz; David Z. Shamritsky; Sebastian Rilk; Kyle N. Kunze; Maximilian M. Mueller; Bryce Demopoulos; Carl W. Imhauser; Gregory S. DiFelice (The American Journal of Sports Medicine, 2026)
Background: The medial collateral ligament (MCL) is the most frequently injured knee ligament. MCL repair is a surgical technique intended to acutely reduce medial side laxity that can be performed in isolation or combined with suture augmentation (SA). Purpose: To assess the effect of MCL repair with and without SA on (1) valgus laxity and anteromedial rotational laxity and (2) force carried by the anterior cruciate ligament (ACL) and (3) to quantify load-sharing between the MCL repair and SA components. Study Design: Controlled laboratory study. Methods: Seven cadaveric knees were tested using a 6 degrees of freedom robotic manipulator in 4 states: (1) intact, (2) MCL cut, (3) isolated MCL repair, and (4) MCL repair combined with SA. Valgus laxity and anteromedial rotational laxity were measured at 0°, 15°, 30°, and 90° of flexion. In situ ACL force and forces carried by the MCL repair components were assessed at peak valgus moment using principle of superposition. Results: Valgus laxity after isolated MCL repair was greater than the intact state at all flexion angles >0° ( P ≤ .01). The addition of SA to MCL repair significantly reduced valgus laxity at 15° and 30° of flexion only ( P ≤ .02). Anteromedial rotational laxity after both MCL repairs was greater than the intact state at 90° of flexion ( P < .01), whereas no differences were detected at 0° and 30°. For both MCL repairs, ACL force was less than in the MCL cut state and did not differ from the intact state. In situ forces carried by the repair and SA components did not differ for the MCL repair combined with SA. Conclusion: Both MCL repair with and without SA reduced ACL force relative to the MCL cut state. Addition of SA to MCL repair resulted in less residual valgus laxity but not less anteromedial rotational laxity. Clinical Relevance: These findings suggest that MCL repair may reduce medial side laxity and partially offload the ACL relative to the MCL cut state. This is particularly important for treatment of combined ACL and MCL injuries, where the protection of the ACL graft or repair is most important immediately after surgery.